Employee performance reward and recognition inequity in the Western Cape Provincial Department of Transport and Public Works - Jansen, M. R.; Hlongwane, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Performance reward amongst employees in the Western Cape Department of Transport and Public Works (WCPDTPW) has been viewed with mixed reactions as a result of fundamental discrepancies associated with the process. The aim of this paper is to explore employee perspectives in relation to performance reward and recognition discrepancies between the lower skilled and highly employees in the Western Cape Provincial Department of Transport and Public Works. Equity theory is applied to explain how perceived inequity in terms of outcomes or rewards could affect employees' motivation to perform in the future. Qualitative research methodology was utilised whereby semi-structured interviews were employed to collect data. A sample of sixteen research participants was selected from the WCPDTPW using a purposive sampling strategy. Data were collected through face-to-face semi-structured interviews. Collected data were analysed using qualitative content analysis. The findings of the paper revealed that participants had negative perceptions concerning performance appraisal and rewards. Moreover, the management of the performance appraisal process is regarded as ineffective and unfair. This process has revealed fundamental performance reward discrepancies between lower-skilled employees and highly skilled employees. Therefore, this paper recommend that the WCPDTPW should also consider non-financial rewards for good performance as a token of appreciation and a means of keeping employees motivated. Moreover, supervisors and managers who are bequeathed with the responsibility of evaluating employee performance should be trained on the ethical considerations of performance appraisal to eliminate bias. Finally, this paper contributes to the body of knowledge and literature with regard to understanding complex issues associated with performance management systems, in particular, the employee performance reward and recognition.
Journal article published in The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Management; Performance appraisal; Performance management; Performance management system; Reward; Employees -- Rating of; Goal setting in personnel management; Performance -- Management; Performance standards